POLA ANTISIPASI KERAWANAN PANGAN DAN PERAN KELEMBAGAAN LOKAL PADA DAERAH TERPENCIL DI KABUPATEN KONAWE - Setsmy Setsmy; Ayub M. Padangaran; Ine Fausayana (Jurnal Sosio Agribisnis, 2018)
Study aim are: find out the level of food insecurity in Asinua distric of Awua Jaya Village Konawe Regency; to know the pattern of anticipation to food insecurity in remote village; to know the role of local institution toward the pattern of anticipation food insecurity that the communityhas done. This study was conducted in the village of Awua Jaya sub-district Asinua regency konawe March-July 2017. The result of study indicate that food insecurity in Asinua sub-distric is still in medium category tahat is at number three (3), where society experiencing food shortage about 3 month; the pattern of food insecurity anticipation in Awua Jaya village can be done in 2 ways, namely for the long term by increasing the productivity of rice crops through improving technology production and increasing the frequency of planting from one time to 2 time a year on irrigation repair conditions; and in the short term with the aid of food in the famine period from March to April each year. P3A intitutions  have no institution related to food insecurity are transmigation service, food crop service, food security agency, farmer group and institutional P3A. The role of such institution has not existed except the transmigration offices that channel raskin 15 kg/3 months so it can not overcome food insecurity.Keywords: food insecurity; patterns of anticipation; the role of local institusions